A STUDY OF RELATION BETWEEN CONGENITAL JAUNDICE AND SOME BIOCHEMICAL PARAMETERS IN NEWBORNS IN NINEVEH GOVERNORATE - Sana Abdulilah Abdulmawjood (Web of Journals Publishing, 2024)
The research was conducted at Al-Kahlaa Educational Hospital, which specializes in obstetrics and pediatrics and is located in Nineveh Governorate. The researchers carried out the study from August 1, 2022, to March 30, 2023. The study included a follow-up of newborns, comprising males (54) and females (26), aged between one day and ten days who had neonatal jaundice. After classifying the cases based on gender, the researchers compared these groups based on gestational age and weight. The analysis of the research data revealed a statistically significant difference (p < 0.05) in the incidence of congenital jaundice between males (67.5%) and females (32.5%). Additionally, there was a notable variation with a statistical significance level below 0.05 in the total bilirubin levels in males. The results indicate a significant increase (p ≤ 0.05) in the incidence of neonatal jaundice among groups with a gestational age of at least 36 weeks (52.5%). These groups (28–31) and (32–35) weeks of gestation recorded incidence rates of 12.5% and 40%, respectively, compared to the (36-39) weeks group, which recorded an incidence rate of 47.5%. However, there was no significant difference in total bilirubin levels between the (32–35) weeks group and the (28–31) and (36-39) weeks groups, with concentrations of (4.07 ± 18.13), (3.64 ± 15.12), and (3.12 ± 15.81), respectively. Statistics revealed a significant decline in weight among individuals with a certain gestational age, specifically 28–31 weeks, with a value of (0.45 ± 1.92). When compared to the gestational age groups of 32–35 and 36–39 weeks, the weight decline was greater, with values of (0.48 ± 2.62) and (0.58 ± 2.78), respectively. The incidence rates of jaundice in these groups were 15% and 48.75%, respectively, compared to 36.25% in the group weighing over 3 kg. Statistical analyses also showed a significant increase in total bilirubin concentration in the group weighing 2-2.9 kg (4.14 ± 17.20) compared to the 1-1.9 kg and over 3 kg groups (3.40 ± 15.40 and 3.28 ± 16.44, respectively). The results showed a significant increase in the activity level of collagen peptide-III (PIIINP) at a probability level (p ≤ 0.05) in females (0.01 ± 18.51) compared to males (0.08 ± 10.32).
Keywords: congenital jaundice, bilirubin, procollagen-III peptide.